Shortcoming, problems and analytical comparison for flooding-based search techniques in unstructured P2P networks. - Barjini, Hassan; Othman, Mohamed; Ibrahim, Hamidah; Udzir, Nur Izura (Springer, 2011)
Peer-to-Peer networks attracted a significant amount of interest because of their capacity for resource sharing and content distribution. Content distribution applications allow personal computers to function in a coordinated manner as a distributed storage medium by contributing, searching, and obtaining digital content. Searching in unstructured P2P networks is an important problem, which has received considerable research attention. Acceptable searching techniques must provide large coverage rate, low traffic load, and optimum latency. This paper reviews flooding-based search techniques in unstructured P2P networks. It then analytically compares their coverage rate, and traffic overloads. Our simulation experiments have validated analytical results.